Exploring the origin of p-type half-metallic ferromagnetism in beryllium doped alkali based perovskites. (September 2019) - Mahmood, Q.; Ul Haq, Bakhtiar; Yaseen, M.; Shahid, Atiba; Laref, A.
Abstract: The thermodynamic stability and half-metallic ferromagnetism of alkali-based beryllium perovskites XBeO3 (X = Li, Na, K, Rb, and Cs) in cubic phase have been analyzed by the first-principles approach. Our results show that more energy is released in the ferromagnetic (FM) phase than the antiferromagnetic (AFM) phase during optimization, revealing the FM phase more stable than the AFM state. Moreover, the thermodynamic, structural and mechanical stabilities in FM state has been confirmed by the enthalpy of formation, tolerance factor,  and Born stability criteria for cubic structured perovskites. The Heisenberg classical model has been used to predict the Curie temperature and spin polarization. The hole mediated double-exchange mechanism illustrates spin-coupling based half-metallic ferromagnetism that leads to XBeO3 as potential materials for spintronic device fabrication. The strong hybridization between the atomic states of 16-atom supercell, especially, the p-p coupling of p -X and p -O yields the total magnetic moment 3μB /unit cell. Highlights: In this paper, we explored the thermodynamic stability and half-metallic ferromagnetism of alkali-based beryllium perovskites XBeO3 (X = Li, Na, K, Rb, and Cs) in framework of density functional theory. The following are the novelty features of this work Investigations of thermodynamic stability of alkali-based beryllium perovskites XBeO3 (X = Li, Na, K, Rb, and Cs). Investigations of origin of half-metallic ferromagnetism. Investigations of electronic properties and spin polarized density of states.